(untitled) (Psychology Travelogs, 2025)
Student youth represent a strategically important social segment that forms the intellectual, economic, and cultural potential of a state. Crises accelerate the process of forming and transforming values among students, making the development of national self-awareness and identity particularly relevant. National self-awareness is a multifaceted phenomenon encompassing an individual’s understanding of their belonging to a nation, awareness of its history, culture, language, and traditions, and active participation in civic life. Research distinguishes between national identity and national self-awareness, where the former is based on cultural and civic-political traditions, shared interests, and national development perspectives, while the latter involves a more profound self-perception and reflection on national belonging. Education plays a crucial role in shaping national self-awareness. The study used the Delphi method to assess key aspects of national self-awareness development among students. Findings indicate that ethnic identity, critical thinking, value orientations, and empathy were the most significant characteristics contributing to national self-awareness. Preliminary findings suggest that CBT techniques effectively enhance students’ national self-awareness by fostering self-reflection, cognitive restructuring, and emotional regulation. These insights underscore the importance of integrating psychological interventions into educational programs to strengthen national identity and cultural cohesion among student youth.